Pengaruh Brand Image dan Kualitas Produk terhadap Pengambilan Keputusan Smartphone Samsung - David Ali Syahrudin; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The development of information technology can lead consumers to quickly find out information about the existence of a product. Companies are required to provide information about their products correctly so it gets a positive response from consumers. Marketing strategies do companies is to shape the brand image and improve product quality. The main problem in this research is about ups and downs of target achievement is never reached in 2011-2015 that is not optimal. This research aims to identify that the influence of brand image and the product quality of the decision of Smartphone Samsung.This study aims to determine the influence of service quality. Whith survey approach, which requires sample of population and questioner as a means of data collection. This research is conducted to 100 responders which buy Smartphone Samsung. Technique of sample is purposive sampling. The analysis method used is a correlation coefficient, the coefficients determined, linear regression simple, linear regression double, T test and F test with program SPSS version 16.Based on the result analysis, brand image and product quality are able to explain the variables of buying decision as 92,1% while brand image has 16,4% and product quality 92,0%. Brand Image together with product quality have significant influenced toward buying decision.The conclusion of this research indicated that brand image and product quality partially and simultaneously has an influence on the making decision Smartphone Samsung. Based on the result, advice for PT. Samsung Group have to find a variation of Smartphone Samsung to improve the brand image and retaining product quality